Pharmacokinetics/pharmacodynamics, safety, and tolerability of fosaprepitant for the prevention of chemotherapy‐induced nausea and vomiting in pediatric cancer patients. Issue 6 (21st March 2019) - Mora, Jaume; Valero, Miguel; DiCristina, Cara; Jin, Mandy; Chain, Anne; Bickham, Kara
Abstract: Background: Current antiemetic regimens are less effective in children than in adults. Fosaprepitant was recently approved for prevention of chemotherapy‐induced nausea and vomiting (CINV) in children aged six months and older. Procedure: The pharmacokinetic (PK)/pharmacodynamic (PD) profile, safety, and tolerability of a single intravenous dose of fosaprepitant administered concomitantly with ondansetron with/without dexamethasone were evaluated in pediatric patients with cancer receiving emetogenic chemotherapy. PK/PD from three doses of fosaprepitant (3.0, 1.2, and 0.4 mg/kg, up to 150, 60, and 20 mg, respectively) were compared with placebo in 2‐ to 17‐year‐old subjects; an open‐label amendment evaluated a fourth dose (5.0 mg/kg, up to 150 mg) in those under 12 years old. Historical adult PK data were used for comparison. Efficacy was measured as an exploratory endpoint. Results: PK data were evaluable for 167/234 subjects who completed cycle one. Aprepitant exposures were dose proportional; adolescents (12 to 17 years) receiving fosaprepitant 150 mg had exposures similar to adults at the same dose. Higher weight‐normalized doses (5 mg/kg) were necessary for children aged < 12 years to achieve comparable adult exposures. The adverse event profile was typical of cancer patients receiving emetogenic chemotherapy. Drug‐related adverse events were reported in 16 (6.8%) subjects, with hiccups being most common ( n  = 5; 2.1%). Conclusions: Intravenous fosaprepitant was well tolerated by pediatric subjects with cancer, and dose‐proportional exposures were observed. Subjects < 12 years old required higher doses to achieve comparable adult exposures.